Analisis Manajemen Kepemimpinan Perempuan dan Beban Kerja Staf Pegawai Administrasi - Nurani Alawiyah; Darmawan Yudhanegara (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
People are the key to the success of an organization. With leadership management and the workload of village administrative staff, these are two important aspects that need to be considered in the implementation of village government. Good leadership management will be able to create a conducive and productive work environment, while a balanced workload will be able to improve employee performance. The aim of this research is to analyze women's leadership management and the workload on administrative staff in the village of Saguling, Saguling district, West Bandung district and focus on leadership management which can reduce the workload on administrative staff in Saguling village. With this type of Qualitative Research, the research informants are the village head and administrative staff of Saguling village, data collection using documentation, observation and interview techniques. The data analysis used consists of data reduction, data presentation, and drawing conclusions. From the research results, it is known that the village head as a female leader can develop appropriate management strategies to manage the workload of administrative staff, including appropriate task delegation, efficient work systems, provision of adequate support and resources, as well as the use of appropriate female leadership styles. situation. By paying attention to the leadership style and internal and external factors, the village head can improve the welfare and performance of staff in carrying out their duties and one of them is serving the community more effectively and efficiently.